Identification of evolutionarily conserved downstream core promoter elements required for the transcriptional regulation of Fushi tarazu target genes - Shir-Shapira, Hila (PLoS One, 2019)
The regulation of transcription initiation is critical for developmental and cellular processes. RNA polymerase II (Pol II) is recruited by the basal transcription machinery to the core promoter where Pol II initiates transcription. The core promoter encompasses the region from -40 to +40 bp relative to the +1 transcription start site (TSS). Core promoters may contain one or more core promoter motifs that confer specific properties to the core promoter, such as the TATA box, initiator (Inr) and motifs that are located downstream of the TSS, namely, motif 10 element (MTE), the downstream core promoter element (DPE) and the Bridge, a bipartite core promoter element. We had previously shown that Caudal, an enhancer-binding homeodomain transcription factor and a key regulator of the Hox gene network, is a DPE-specific activator. Interestingly, pair-rule proteins have been implicated in enhancer-promoter communication at the engrailed locus. Fushi tarazu (Ftz) is an enhancer-binding homeodomain transcription factor encoded by the ftz pair-rule gene. Ftz works in concert with its co-factor, Ftz-F1, to activate transcription. Here, we examined whether Ftz and Ftz-F1 activate transcription with a preference for a specific core promoter motif. Our analysis revealed that similarly to Caudal, Ftz and Ftz-F1 activate the promoter containing a TATA box mutation to significantly higher levels than the promoter containing a DPE mutation, thus demonstrating a preference for the DPE motif. We further discovered that Ftz target genes are enriched for a combination of functional downstream core promoter elements that are conserved among Drosophila species. Thus, the unique combination (Inr, Bridge and DPE) of functional downstream core promoter elements within Ftz target genes highlights the complexity of transcriptional regulation via the core promoter in the transcription of different developmental gene regulatory networks.